2004
DOI: 10.1111/j.0956-7976.2004.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

When Strangers Pass

Abstract: Using functional magnetic resonance imaging (fMRI), we investigated brain activity evoked by mutual and averted gaze in a compelling and commonly experienced social encounter. Through virtual-reality goggles, subjects viewed a man who walked toward them and shifted his neutral gaze either toward (mutual gaze) or away (averted gaze) from them. Robust activity was evoked in the superior temporal sulcus (STS) and fusiform gyrus (FFG). For both conditions, STS activity was strongly right lateralized. Mutual gaze e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(95 citation statements)
references
References 32 publications
5
86
2
Order By: Relevance
“…Some studies show that pSTS responds more to direct gaze (Pelphrey et al, 2004), averted gaze (Hoffman & Haxby, 2000;Puce et al, 1998), is equivalent for direct and averted gaze (Wicker et al, 1998), and some show no response in STS (George, Driver, & Dolan, 2001;Kawashima et al, 1999). These conflicting results may also account for the absence of STS sensitivity to gaze direction in the current study.…”
Section: Gaze Directioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Some studies show that pSTS responds more to direct gaze (Pelphrey et al, 2004), averted gaze (Hoffman & Haxby, 2000;Puce et al, 1998), is equivalent for direct and averted gaze (Wicker et al, 1998), and some show no response in STS (George, Driver, & Dolan, 2001;Kawashima et al, 1999). These conflicting results may also account for the absence of STS sensitivity to gaze direction in the current study.…”
Section: Gaze Directioncontrasting
confidence: 56%
“…Within this network, the STS and intraparietal sulcus (IPS) have been associated with different functional processes during gaze perception (Nummenmaa, Passamonti, Rowe, Engell, & Calder, 2010;Hoffman & Haxby, 2000). Anterior and posterior segments of STS (aSTS and pSTS, respectively) are associated with processing gaze direction (Calder et al, 2007;Pelphrey, Viola, & McCarthy, 2004;Hooker et al, 2003;Pelphrey, Singerman, Allison, & McCarthy, 2003;Puce, Allison, Bentin, Gore, & McCarthy, 1998;Wicker, Michel, Henaff, & Decety, 1998;Perrett et al, 1985). In contrast, IPS has been shown to respond specifically to attention-shifting aspects of gaze perception (Materna, Dicke, & Thier, 2008;Hietanen, Nummenmaa, Nyman, Parkkola, & Hämäläinen, 2006) and the observerʼs tendency to shift gaze and attention in the same direction as the observed individual (Driver et al, 1999;Langton & Bruce, 1999;Friesen & Kingstone, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Right STG function is of major interest in neuroscientific research on brain and mind interaction. Theory of mind studies and research on social interaction and empathic behavior throw critical light on tasks involving the right STG (Carr et al, 2003;Leslie, Johnson-Frey, & Grafton, 2004;Pelphrey, Viola, & McCarthy, 2004;Vö llm et al, 2006). Because the right STG is critically involved in social cognition and social perception, volume loss and STG dysfunction may underlie social dysfunction in psychopathy and indicate that right STG dysfunction could help to explain the psychopathic lack of empathy Mü ller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies in adults, the STS, middle temporal gyrus, and inferior parietal lobule were sensitive to the intentions underlying the stimulus character's eye movements. It has also been demonstrated that the STS region plays a critical role in processing eye gaze signals of approach and avoidance [50]. These findings suggest that achieving joint attention, a pivotal skill in social cognition, is facilitated by the analysis of sensory cues in the STS.…”
Section: Social Perception and Social Cognition: Implication Of The Tmentioning
confidence: 91%